2021
DOI: 10.1038/s41598-021-97574-z
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of drought and rainfall events of different patterns on watershed systems

Abstract: The increase in extreme climate events such as flooding and droughts predicted by the general circulation models (GCMs) is expected to significantly affect hydrological processes, erosive dynamics, and their associated nonpoint source (NPS) pollution, resulting in a major challenge to water availability for human life and ecosystems. Using the Hydrological Simulation Program–Fortran model, we evaluated the synergistic effects of droughts and rainfall events on hydrology and water quality in an upstream catchme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 85 publications
0
16
0
1
Order By: Relevance
“…Large PET variability manifests a rapid rate of soil water from land surface to the atmosphere (Qiu et al., 2021), contributing to the local transition from dry to wet periods. Large precipitation variability yields highly non‐uniform precipitation distributions (W. Zhang et al., 2021), and increases the intrinsic likelihood of dry and wet extremes (Swain et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Large PET variability manifests a rapid rate of soil water from land surface to the atmosphere (Qiu et al., 2021), contributing to the local transition from dry to wet periods. Large precipitation variability yields highly non‐uniform precipitation distributions (W. Zhang et al., 2021), and increases the intrinsic likelihood of dry and wet extremes (Swain et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, floods can limit the photosynthetic activity of the blooms by flushing (depending on the residence time of lakes) the biomass from the lakes, while also increasing nutrient emissions due to sewage overflows from urban areas. In addition, Qiu et al (2021) reported complex interactions of drought and precipitation events leading to the rapid flushing of accumulated sediments and nutrients influenced by soil water content, antecedent drought duration and other climatic variables. (Reichwaldt and Ghadouani 2012) analysed the effect of rainfall patterns on toxic cyanobacterial blooms and reported that: (i) increased frequency will reduce bloom occurrences due to disturbances in stratification, however (ii) the length of the dry period before rainfall combined with the intensity decides the ultimate effect of nutrient enrichment in lakes.…”
Section: Hydro-climatologymentioning
confidence: 99%
“…Descobertas recentes apontam que a alta variabilidade climática como a ocorrência de episódios de seca extrema e chuvas intensas de modo sinérgico pode causar degradações ambientais em bacias hidrográficas (Qiu et al, 2021). Os mesmos pesquisadores ainda alertam que tal cenário pode comprometer a segurança hídrica.…”
Section: El Niño E Dipolo Positivounclassified